2023
DOI: 10.7759/cureus.44277
|View full text |Cite
|
Sign up to set email alerts
|

Boric Acid Exhibits Anticancer Properties in Human Endometrial Cancer Ishikawa Cells

Ayşe Çakır Gündoğdu,
Neziha Senem Arı,
Asiye Höbel
et al.

Abstract: Objective This study aims to explore the potential anti-cancer properties of boric acid (BA) in human endometrial cancer Ishikawa cells by assessing its influence on cell viability, apoptosis, oxidative stress, and inflammatory responses. Methods The impact of BA at concentrations ranging from 2.5 to 100 mM on cell viability was assessed in Ishikawa cells and normal fibroblast L929 cells (used as the control) through the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium brom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(33 reference statements)
0
3
0
Order By: Relevance
“… 35 Moreover, in vitro experiments employing various cell lines, such as Ishikawa cells, illustrated a significant decline in cell proliferation at boric acid concentrations of 40 mM and above. 36 Additionally, our earlier research revealed that treatment with 10.77 mM boric acid in DU‐145 cells led to a noteworthy reduction in cell growth. 37 Collectively, extant literature delineates a trend wherein boron compounds impede cancer cell proliferation beyond a certain concentration threshold.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“… 35 Moreover, in vitro experiments employing various cell lines, such as Ishikawa cells, illustrated a significant decline in cell proliferation at boric acid concentrations of 40 mM and above. 36 Additionally, our earlier research revealed that treatment with 10.77 mM boric acid in DU‐145 cells led to a noteworthy reduction in cell growth. 37 Collectively, extant literature delineates a trend wherein boron compounds impede cancer cell proliferation beyond a certain concentration threshold.…”
Section: Discussionmentioning
confidence: 94%
“…Prior studies have indicated that boric acid, another boron compound, augmented viability in HepG2 cells in a concentration‐dependent manner, exhibiting an IC50 value of approximately 24 mM 35 . Moreover, in vitro experiments employing various cell lines, such as Ishikawa cells, illustrated a significant decline in cell proliferation at boric acid concentrations of 40 mM and above 36 . Additionally, our earlier research revealed that treatment with 10.77 mM boric acid in DU‐145 cells led to a noteworthy reduction in cell growth 37 .…”
Section: Discussionmentioning
confidence: 98%
“…In vivo and in vitro studies have provided evidence of the prophylactic and therapeutic effectiveness of boric acid in rats as well as highlighting its anti‐cancer properties in human endometrial cancer Ishikawa cells and DU‐145 prostate cancer cells. 17 , 22 , 23 Cancer cells are known for producing higher levels of reactive oxygen species (ROS) compared to normal cells, primarily due to disruptions in their redox balance. 24 This imbalance between antioxidant and oxidant molecules in cancer cells provides an opportunity for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%